2022
DOI: 10.3389/fimmu.2022.824278
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein 96 in Peritoneal Dialysis Effluent-Derived Extracellular Vesicles: A Tool for Evaluating Peritoneal Transport Properties and Inflammatory Status

Abstract: BackgroundExtracellular vesicles (EVs) from peritoneal dialysis effluent (PDE), containing molecules such as proteins and microRNAs (miRNAs), may be potential biological markers to monitor peritoneal function or injury. Peritoneal inflammation is an important determinant of peritoneal solute transport rate (PSTR). Thus, the aim of this study is to determine whether the specific proteins capable of evaluating the PSTR could be found in PDE-EVs, and explore the underlying mechanism for the association between PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The fact that EVs can be found in PD effluent offers a glimpse into the pathological state of peritoneal cells. In previous studies, effluent‐derived EVs in patients undergoing PD with high/high average transport (H/HA) or low/low average transport (L/LA) presented distinct protein expression profiles (Fang et al., 2022 ). Our data further demonstrated that proteins in LPD‐EVs are enriched in the pathways relevant to fibrosis and metabolism, suggesting the dynamical alteration of EVs in abdominal cavity microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that EVs can be found in PD effluent offers a glimpse into the pathological state of peritoneal cells. In previous studies, effluent‐derived EVs in patients undergoing PD with high/high average transport (H/HA) or low/low average transport (L/LA) presented distinct protein expression profiles (Fang et al., 2022 ). Our data further demonstrated that proteins in LPD‐EVs are enriched in the pathways relevant to fibrosis and metabolism, suggesting the dynamical alteration of EVs in abdominal cavity microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that PD effluent-derived EVs are positive for the mesothelial marker mesothelin, supporting that mesothelial cells may be one of the sources of these EVs (Bruschi et al, 2021;Fang et al, 2022). However, using single cell marker to determine the source of PD effluent-derived EVs is not sufficient, and the specific cell sources of these EVs remain largely unknown.…”
Section:  Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successively, the researchers validated their results in vitro, showing that GP96 increased the secretion of proinflammatory cytokines (IL-1β, IL-6, TNF-α, and IL-18) in peritoneal derived macrophages and in a PD rat model where the GP96 inhibition reduced peritoneal inflammation response through the reduction of inflammatory cells, cytokines, and chemokines (CCL2, CXCL1, and CXCL2). Their findings suggest that GP96 can be a potential indicator of peritoneal inflammation and PSTR in PD patients [ 62 ]. In the latest years, among the other extracellular vesicles, the analysis of exosomes has earned the greatest interest in the field of new diagnostic and therapeutic possibilities [ 63 ].…”
Section: Proteomics Applied To Extracellular Vesicles and Exosomesmentioning
confidence: 99%
“…These PD effluent-derived EV proteomes showed alteration earlier than peritoneal equilibration test monitoring, suggesting the potential of EV proteins as biomarkers of peritoneal function alteration for patients undergoing PD . Moreover, it has been reported that specific molecular cargo in EVs, such as aquaporin 1 and glycoprotein 96, can be used to evaluate the status of peritoneum. , …”
Section: Introductionmentioning
confidence: 96%